2012
DOI: 10.1590/s1516-35982012000100015
|View full text |Cite
|
Sign up to set email alerts
|

L-glutamine and L-glutamate in diets with different lactose levels for piglets weaned at 21 days of age

Abstract: -This study was developed to evaluate the effects of adding L-glutamine and L-glutamate in diets with no lactose or with 4.0 or 8.0% lactose inclusion for piglets weaned at 21 days old. One hundred and eight piglets with initial weight of 6.12±0.70 kg were allotted in a complete randomized block design, in a 3 × 2 factorial arrangement, with six treatments, six replicates, and three piglets per experimental unit. The experimental diets were supplied from 21 to 35 days. From 36 to 49 days, animals received the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…It is known that small intestine is the site where most nutrients are digested and absorbed (Rivest et al 2000) and colon and caecum are less important (Rudolph et al 1983). Thus sodium butyrate affecting intestine development may also improve nutrient absorption, especially in jejunum (Kotunia et al 2004;Molino et al 2012), and in consequence piglet performance.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that small intestine is the site where most nutrients are digested and absorbed (Rivest et al 2000) and colon and caecum are less important (Rudolph et al 1983). Thus sodium butyrate affecting intestine development may also improve nutrient absorption, especially in jejunum (Kotunia et al 2004;Molino et al 2012), and in consequence piglet performance.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that glutamine has positive effects on piglet growth performance, intestinal morphology, epithelial cell renewal, antioxidant capacity and barrier functions (Wu et al, 1996;Domeneghini et al, 2006;Wang et al, 2008 and2014;Molino et al, 2012;Zhu et al, 2015;Jiang et al, 2017).…”
Section: Glutamine Regulates Intestinal Function Of Weaning Pigsmentioning
confidence: 99%
“…However, results differ regarding the effects of glutamine on intestinal villi height and crypt depth. Some authors verified that glutamine only influences villi height in swine (MOLINO et al, 2012), Nile tilapia juvenile (SILVA et al, 2010) and broilers (BARTELL & BATAL, 2007). Other authors verified that glutamine influences crypt depth (MAIORKA et al, 2000).…”
Section: Resultsmentioning
confidence: 97%
“…The localization of box inside conventional shed was adopted as blocks criteria. Corn and soybean meal diets were formulated to meet broiler requirements (ROSTAGNO et al, 2005) for all nutrients and no anticoccidial agents and antibiotics were used as growth promoters (Table 1). The feeding program adopted had four phases as follows: pre-starter (1 to 7 days old); starter (8 to 21 days old), growth (22 to 35 days old) and finishing phase (36 to 42 days old).…”
Section: Methodsmentioning
confidence: 99%